Solve for x (complex solution)
x=\frac{-\sqrt{39}i+3}{4}\approx 0.75-1.5612495i
x=6
x=\frac{3+\sqrt{39}i}{4}\approx 0.75+1.5612495i
Solve for x
x=6
Graph
Share
Copied to clipboard
2x^{3}-12x^{2}+12=3\left(x-4\right)^{2}
Variable x cannot be equal to 4 since division by zero is not defined. Multiply both sides of the equation by \left(x-4\right)^{2}.
2x^{3}-12x^{2}+12=3\left(x^{2}-8x+16\right)
Use binomial theorem \left(a-b\right)^{2}=a^{2}-2ab+b^{2} to expand \left(x-4\right)^{2}.
2x^{3}-12x^{2}+12=3x^{2}-24x+48
Use the distributive property to multiply 3 by x^{2}-8x+16.
2x^{3}-12x^{2}+12-3x^{2}=-24x+48
Subtract 3x^{2} from both sides.
2x^{3}-15x^{2}+12=-24x+48
Combine -12x^{2} and -3x^{2} to get -15x^{2}.
2x^{3}-15x^{2}+12+24x=48
Add 24x to both sides.
2x^{3}-15x^{2}+12+24x-48=0
Subtract 48 from both sides.
2x^{3}-15x^{2}-36+24x=0
Subtract 48 from 12 to get -36.
2x^{3}-15x^{2}+24x-36=0
Rearrange the equation to put it in standard form. Place the terms in order from highest to lowest power.
±18,±36,±9,±6,±12,±\frac{9}{2},±3,±2,±4,±\frac{3}{2},±1,±\frac{1}{2}
By Rational Root Theorem, all rational roots of a polynomial are in the form \frac{p}{q}, where p divides the constant term -36 and q divides the leading coefficient 2. List all candidates \frac{p}{q}.
x=6
Find one such root by trying out all the integer values, starting from the smallest by absolute value. If no integer roots are found, try out fractions.
2x^{2}-3x+6=0
By Factor theorem, x-k is a factor of the polynomial for each root k. Divide 2x^{3}-15x^{2}+24x-36 by x-6 to get 2x^{2}-3x+6. Solve the equation where the result equals to 0.
x=\frac{-\left(-3\right)±\sqrt{\left(-3\right)^{2}-4\times 2\times 6}}{2\times 2}
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. Substitute 2 for a, -3 for b, and 6 for c in the quadratic formula.
x=\frac{3±\sqrt{-39}}{4}
Do the calculations.
x=\frac{-\sqrt{39}i+3}{4} x=\frac{3+\sqrt{39}i}{4}
Solve the equation 2x^{2}-3x+6=0 when ± is plus and when ± is minus.
x=6 x=\frac{-\sqrt{39}i+3}{4} x=\frac{3+\sqrt{39}i}{4}
List all found solutions.
2x^{3}-12x^{2}+12=3\left(x-4\right)^{2}
Variable x cannot be equal to 4 since division by zero is not defined. Multiply both sides of the equation by \left(x-4\right)^{2}.
2x^{3}-12x^{2}+12=3\left(x^{2}-8x+16\right)
Use binomial theorem \left(a-b\right)^{2}=a^{2}-2ab+b^{2} to expand \left(x-4\right)^{2}.
2x^{3}-12x^{2}+12=3x^{2}-24x+48
Use the distributive property to multiply 3 by x^{2}-8x+16.
2x^{3}-12x^{2}+12-3x^{2}=-24x+48
Subtract 3x^{2} from both sides.
2x^{3}-15x^{2}+12=-24x+48
Combine -12x^{2} and -3x^{2} to get -15x^{2}.
2x^{3}-15x^{2}+12+24x=48
Add 24x to both sides.
2x^{3}-15x^{2}+12+24x-48=0
Subtract 48 from both sides.
2x^{3}-15x^{2}-36+24x=0
Subtract 48 from 12 to get -36.
2x^{3}-15x^{2}+24x-36=0
Rearrange the equation to put it in standard form. Place the terms in order from highest to lowest power.
±18,±36,±9,±6,±12,±\frac{9}{2},±3,±2,±4,±\frac{3}{2},±1,±\frac{1}{2}
By Rational Root Theorem, all rational roots of a polynomial are in the form \frac{p}{q}, where p divides the constant term -36 and q divides the leading coefficient 2. List all candidates \frac{p}{q}.
x=6
Find one such root by trying out all the integer values, starting from the smallest by absolute value. If no integer roots are found, try out fractions.
2x^{2}-3x+6=0
By Factor theorem, x-k is a factor of the polynomial for each root k. Divide 2x^{3}-15x^{2}+24x-36 by x-6 to get 2x^{2}-3x+6. Solve the equation where the result equals to 0.
x=\frac{-\left(-3\right)±\sqrt{\left(-3\right)^{2}-4\times 2\times 6}}{2\times 2}
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. Substitute 2 for a, -3 for b, and 6 for c in the quadratic formula.
x=\frac{3±\sqrt{-39}}{4}
Do the calculations.
x\in \emptyset
Since the square root of a negative number is not defined in the real field, there are no solutions.
x=6
List all found solutions.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}